The Method of research of adhesion strength and wearproofness of polymeric composition coverages - Дудчак, В.П.; Дудчак, Т.В.; Остапенко, Р.М. (Problems of Tribology, 2014)
In the article the presented method of research of adhesion strength and wearproofness of polymeric composition coverages. Optimum composition of additions is certain for creation of polymeric composition